2018
DOI: 10.1503/cmaj.171391
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions for managing multiple high-burden chronic diseases in older adults: a systematic review and meta-analysis

Abstract: PROSPERO-CRD42014014489.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(107 citation statements)
references
References 65 publications
(87 reference statements)
2
95
0
2
Order By: Relevance
“…46 Although findings are mixed, Health TAPESTRY is aligned with accepted guidance for personal care planning, 47,48 providing patient-centred or goal-directed care for older adults who are managing multiple chronic conditions 49 and Starfield principles of primary care, [50][51][52] and, for people with chronic diseases, care-coordination strategies that improve health and outcomes. 53 The intervention is well aligned with redesigns of the health care system underway in Canada and elsewhere 21,[54][55][56][57] and incorporates key elements recommended by the World Health Organization for integrated health care for older people. 24 Volunteers showed great enthusiasm for and a sense of purpose regarding their role.…”
Section: Discussionmentioning
confidence: 99%
“…46 Although findings are mixed, Health TAPESTRY is aligned with accepted guidance for personal care planning, 47,48 providing patient-centred or goal-directed care for older adults who are managing multiple chronic conditions 49 and Starfield principles of primary care, [50][51][52] and, for people with chronic diseases, care-coordination strategies that improve health and outcomes. 53 The intervention is well aligned with redesigns of the health care system underway in Canada and elsewhere 21,[54][55][56][57] and incorporates key elements recommended by the World Health Organization for integrated health care for older people. 24 Volunteers showed great enthusiasm for and a sense of purpose regarding their role.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing administrators can conduct special geriatric survey conduct various programmes related to the welfare of the old age people and develop necessary educational material [14]. Similar study may be replicated on large sample and comparative study may be conducted between urban and rural community [15,16].…”
Section: Association Of Knowledge Scores Of Elderly Population With Smentioning
confidence: 99%
“…18 A recent systematic review and metaanalysis concluded that multidisciplinary care coordination interventions for patients with MCCs appear to have the potential for improving primary and secondary outcomes, including care utilization. 19 The effects of such care programs are different for each type of model and disease. Further evidence is needed to establish if multidisciplinary care interventions affect health-care utilization patterns in patients with specific disease combinations.…”
Section: Introductionmentioning
confidence: 99%